Windows 10 for the internet of things - Bell, Charles (Apress, 2016)
Develop applications for the Internet of Things on the Raspberry Pi using your Windows and .NET programming skills. This book helps you learn everything you need to know about Windows IoT Core in order to develop Windows apps that run on the Pi. Interest in connected devices is exploding, already including things such as thermostats and light bulbs. Going right along with the explosion of such devices is a growth in interest in how to program for them and how to capture and analyze the data they have to offer. Microsoft is responding to this trend with Windows 10 IoT Core, an edition of Windows aimed specifically at the Internet of Things. This book shows .NET programmers how they can transfer skill sets from desktop programming and apply those same skill sets now to programming for the Internet of Things. Microsoft's release of Windows IoT Core is groundbreaking in how it makes the Raspberry Pi and Internet of Things programming accessible to Windows developers. Now it's possible to develop for the Raspberry Pi using native Windows and all the related programming skills that Windows programmers have learned from developing desktop and mobile applications. Windows 10 becomes a gateway by which many can experience hardware and Internet of Things development who may never have had the opportunity otherwise. Windows 10 for the Internet of Things presents a set of example projects covering a wide range of techniques designed specifically to jump start your own Internet of Things creativity. Even savvy Windows programmers require help to get started with hardware development. Windows 10 for the Internet of Things provides just the help you need to get started in putting your Windows skills to use in a burgeoning new world of development for small devices that are ubiquitously connected to the Internet. With this book you will learn Windows 10 on the Raspberry Pi and how to: Read sensor data and control actuators Connect to and transmit data into the cloud Remotely control your devices from any web browser Develop IOT applications under Windows using C# and Python Store your IOT data in a database for later analysis.